Biologically enhanced dissolution of a pyrite-rich black shale concentrate - Tasa, Andrus; Vuorinen, Antti; Garcia Jr., Oswaldo [UNESP]; Tuovinen, Olli H. (My University, 1997)
The acid leaching of a pyrite-rich black shale concentrate (7% S) was tested in this study. The experiments were performed at 5-30% pulp densities and with inoculations of Fe- and S-oxidizing thiobacilli (Thiobacillus ferrooxidans and Thiobacillus thiooxidans). Cultures supplemented with S0 showed strong acid production, with final pH values of 0.9 in T. ferrooxidans cultures and 0.4-0.5 in the presence of T. thiooxidans. Fe dissolution was pronounced in the T. ferrooxidans culture whereas T. thiooxidans did not dissolve Fe from the black shale. Total dissolved Fe concentrations were 3 to 50 times higher in the cultures inoculated with T. ferrooxidans when compared to T. thiooxidans and sterile controls. The dissolution of Mo was enhanced in the inoculated cultures as compared with the chemical controls. With V, Si, and Al this effect was not as pronounced but was still discernible in solutions acidified by bacterial oxidation of S0. The leaching experiments suggested that the black shale was inhibitory to the inocula. The inhibition was related to the pulp density and was associated with the leach solution. The inhibition could be completely alleviated by replacing the leach solution.
Keywords: Bioleaching; Iron oxidation; Pyrite oxidation; Sulfur oxidation; Thiobacillus